Developing an Army Strategy for Building Partner Capacity for Stability Operations - Marquis, Jefferson P. (RAND Corporation, 2010)
The U.S. government is facing the dual challenge of building its own interagency capacity for conducting stability operations while simultaneously building partner capacity (BPC) for stability operations. This study finds that although BPC and stability operations are receiving a good deal of attention in official strategy and planning documents, insufficient attention is being paid to the details of an integrated strategy.